Epstein–Barr virus shedding by astronauts during space flight - Pierson, D.L.; Stowe, R.P.; Phillips, T.M.; Lugg, D.J.; Mehta, S.K. (Brain, behavior, and immunity, 2005)
Patterns of Epstein–Barr virus (EBV) reactivation in 32 astronauts and 18 healthy age-matched control subjects were characterized by quantifying EBV shedding. Saliva samples were collected from astronauts before, during, and after 10 space shuttle missions of 5–14 days duration. At one time point or another, EBV was detected in saliva from each of the astronauts. Of 1398 saliva specimens from 32 astronauts, polymerase chain reaction analysis showed that 314 (23%) were positive for EBV DNA. Examination by flight phase showed that 29% of the saliva specimens collected from 28 astronauts before flight were positive for EBV DNA, as were 16% of those collected from 25 astronauts during flight and 16% of those collected after flight from 23 astronauts. The mean number of EBV copies from samples taken during the flights was 417 per mL, significantly greater ( p < .05) than the number of viral copies from the preflight (40) and postflight (44) phases. In contrast, the control subjects shed EBV DNA with a frequency of 3.7% and mean number of EBV copies of 40 per mL of saliva. Ten days before flight and on landing day, titers of antibody to EBV viral capsid antigen were significantly ( p < .05) greater than baseline levels. On landing day, urinary levels of cortisol and catecholamines were greater than their preflight values. In a limited study ( n = 5), plasma levels of substance P and other neuropeptides were also greater on landing day. Increases in the number of viral copies and in the amount of EBV-specific antibody were consistent with EBV reactivation before, during, and after space flight.